Association between maternal factors and survival patterns of children, in rural Kwazulu-Natal, South Africa, 2004-2011 - Makumi, Anne Njeri (My University, 2014)
Globally, child mortality is a great concern, especially in resource-limited settings. The Millennium Development Goal (MDG) 4 was set with an aim to reduce under-5 child mortality by two-thirds between 1990 and 2015. This study examines mortality trends in infants, 1-4 and above 5-year-old children in rural KwaZulu-Natal, South Africa, the causes of death as well as the association of maternal HIV status and Antiretroviral Treatment (ART) usage to child mortality. We use a longitudinal birth cohort study design of children born between 1st January 2004 and 31st December 2010, in the Africa Centre Demographic Surveillance Area (DSA) in rural KwaZulu-Natal, South Africa. Children had to have been resident in the DSA at the time of birth. A total of 12,413 children born in the study period were eligible for this study. The main outcome measure was mortality either in infancy, the 1-4 year period or at 5 and above years of age, while assessing its association with maternal HIV and Antiretroviral Treatment uptake (ART) status on a time-varying basis. A total of 619 children died during the study period and mortality was observed to be highest in the infant group with 67% of the children dying in infancy. Fifteen percent of mothers were HIV positive at the time of birth of the child, about 59% were HIV negative while the HIV status of the rest was unknown. There was a three-fold increase in mortality observed for both infants and 1-4 year olds, who had mothers who were HIV infected compared to children whose mothers were HIV negative (p<0.05). Children whose mothers were on Antiretroviral Treatment (ART) however had a reduced mortality compared to those whose mothers were not on treatment. Infants and 1-4year olds whose mothers HIV status was not reported had a two-fold increase in mortality. Low maternal education, single motherhood, multiple births and parity of four or more children were also associated with increased child mortality. We concluded that although mortality varied by the age of the child, children born to mothers who were HIV positive had higher mortality rates than children born to HIV negative mothers but being on Anti Retroviral Treatment (ART) reduced children mortality. Interventions targeting HIV positive pregnant women and mothers should be carried out in the study area, with specific emphasis on reducing child mortality associated with maternal HIV status.
Keywords: Survival--in infancy & childhood; Infant Mortality